2015
DOI: 10.1093/ehjci/jev217
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac morphology and function reference values derived from a large subset of healthy young Caucasian adults by magnetic resonance imaging

Abstract: This is the first large database of reference ranges for ventricular and atrial functions, volumes, and mass in young Caucasian men and women devoid of cardiovascular disease and risk factors. These data will contribute to improving the accuracy of CMR interpretation for clinical and research applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 37 publications
5
42
2
Order By: Relevance
“…13 This is in concordance with the present findings; the average indexed left atrial volume among patients with either mutation was higher than the normal reported values. 37 However, we found no difference in left atrial volume between the 2 genes.…”
Section: Discussioncontrasting
confidence: 57%
“…13 This is in concordance with the present findings; the average indexed left atrial volume among patients with either mutation was higher than the normal reported values. 37 However, we found no difference in left atrial volume between the 2 genes.…”
Section: Discussioncontrasting
confidence: 57%
“…As expected, we observed strong correlations between measurements obtained within the same platform, but also several interesting inter-platform correlations. As seen in humans whose cardiac parameters strongly correlate with gender, age and ethnicity (Lancellotti, 2014;Caballero et al, 2015;Kawel-Boehm et al, 2015;Le Ven et al, 2016;Petersen et al, 2017), we noticed within the WT group a positive correlation between age and the volume of the OFT relative to the entire heart (% OFT volume; Figure 5C). Furthermore, retrograde OFT flow, which was present in two WT animals, correlated with atrial enlargement.…”
Section: Correlation Analysis Between All Parameters Reveals Previoussupporting
confidence: 68%
“…Differences between the sexes with regard to ventricular parameters has been reported in several studies. 8,14,16,19 Two studies showed no differences between the sexes in LVEDVi, LVESVi, and LVEF after adjustment for BSA. 4,20 Usually, LV and RV volumes are larger in males than in females, even after adjustment for BSA.…”
Section: Discussionmentioning
confidence: 99%
“…In past decades, several studies have reported the normal reference values of LV or RV volume and function in healthy volunteers or subjects without cardiovascular disease. 9,[12][13][14][15][16][17][18][19] Those results provided useful references for evaluation of the structure and function of the heart. However, most of those studies focused on a single ethnicity and included only narrow age ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation